Takhrīj Ḥadīth Ghars Al-Ashjār: Tracing the Greening Spirit Roots in Sunnah Nabawiyyah - Taufiq Hidayat Karim (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
Analyses of the National Disaster Management Agency (BNPB) states that beside weather and environmental typologies, human activities have a significant role in triggering disasters. Quran Surah Al-Rūm verse 41 has justified this idea, and legitimizes that disasters occur because of people’s lack of awareness and self-motivations to take care of the environment. This article seeks to investigate hadith matn to motivate the action of preserving the nature. This article focuses to find out a qualitative hadith in order to gain an appropriate understanding of hadith (fiqh al- ḥadīth). This research is a library research with a content analyses to related documents. In addition, this study applies a simultaneous hadith approach (a simultaneous method) and understanding of thematic hadith (fiqh al-ḥadīth al-mawḍū'i). This paper concludes that the hadith in this question had a quality of hadith ṣaḥīḥ li dzātih and included into mashhūr ḥadīth (popular hadith). This hadith provides a significant role to motivate greening for the preservation of nature.